Measurement Results of a Modular Energy Storage System unevenly Equipped with Li-Ion-Batteries - Schröder, Markus; Henninger, Stefan; Jäger, Johann; Rubenbauer, Hubert (17th Europeans Conference on Power Electronics and Applications, 2015)
The objective of this paper was to present and evaluate measurement results of a battery energy storage system (BESS) that is based on a modular multilevel cascade converter (MMCC). The MMCC was unevenly equipped with lithium-ion batteries. The suggested concept of modular BESS was classified in the context of BESS based on modular converter topologies and was realized in a hardware-setup in laboratory. Therefore, different operation modes of the modular BESS were defined. Four different steady operation points of the entire system were investigated and evaluated. Finally, a concept of an active battery management system (BMS) was proved. It was shown that a modular BESS unevenly equipped with batteries offers several opportunities for BESS applications particularly with regard to the integration of different types of batteries into one single BES
Keywords: Batteries; Energy storage; Multilevel converters; Battery Managements Systems